Simultaneous changes of the spontaneous and stimulus-evoked cortical activity in rats acutely treated with mercuric chloride - Pecze L. (NEUROTOXICOLOGY AND TERATOLOGY, 2004)
In earlier studies of our laboratory and in several other reports, alterations in the electrical activity of the cortex of experimental animals on subchronic mercury (Hg) administration were described. In the present work, simultaneous changes in the spontaneous and stimulus-evoked cortical activity elicited by acute administration of inorganic Hg were evaluated with the aim of finding any correlation of the two, possibly giving insight into the mechanism of the alterations. In young adult male Wistar rats, spontaneous cortical, as well as stimulus-evoked cortical and peripheral nervous activity was recorded, before and after acute administration of 3.5 and 7.0 mg/kg Hg2+ ip. The effects of Hg2+ appeared within 10 min and most became significant over 3 h. On the cortex, slowed spontaneous activity, as well as increased amplitude and latency of the evoked potentials (EPs) was seen, and in the periphery, decreased nerve conduction velocity. These alterations seemed to be consistent with a separate cortical and peripheral axonal effect of Hg. ÂŠ 2003 Elsevier Inc. All rights reserved.